Small bowel water content assessed by MRI in health and disease: a collation of single‐centre studies. Issue 3 (30th October 2021) - Dellschaft, Neele; Hoad, Caroline; Marciani, Luca; Gowland, Penny; Spiller, Robin
Summary: Background: New developments in MRI have allowed the non‐invasive, accurate measurement of the small bowel water content (SBWC). Aims: To collate studies measuring SBWC following ingestion of a range of foods in both health and disease to provide data for adequately powering future studies in this area. Methods: This collation brings together 29 studies including 954 participants (530 healthy, 54 diverticulosis, 255 IBS, 53 functional constipation, 12 cystic fibrosis, 15 Crohn's disease, 20 coeliac disease, 15 scleroderma) which have been carried out in a single centre using comparable study designs. Results: Fasting SBWC (mean 82 [SD 65] mL) shows high variability with a small decline with advancing age (healthy volunteers only; individual patient data). Fasting values are increased in untreated coeliac disease (202 [290] mL, P = 0.004). Post‐prandial SBWC shows less intra‐individual variability than fasting values in healthy volunteers. SBWC is increased by eating, most markedly by high fat meals but also by fibre, both viscous and particulate. Indigestible residue accumulates in late post‐prandial period but empties soon after ingestion of a high calorie meal which produces a significant drop (by 50 [52] mL) in healthy volunteers. The associated fall in SBWC is abnormal in people with cystic fibrosis (SBWC reduced by 10 [121] mL, P = 0.002) and in people with irritable bowel syndrome with diarrhoea (SBWC reduced by 17 [43] mL, P = 0.007). Conclusions: SBWC as assessed by MRI is a valuable biomarker indicating the balance of secretion and absorption in health and disease and the impact of treatments. Abstract : Free small bowel water contents (SBWC) are influenced by dietary components: fat, sugars, fibre. Using MRI, we have directly measured this valuable biomarker indicating the balance of secretion and absorption. We are presenting a collation of data from 29 studies including 954 participants.